A case report of Vibrio furnissii bacteremia and cellulitis in a malnourished patient without an apparent site of entry. Issue 1 (January 2018) - Hashimoto, Takehiro; Takaya, Saho; Kutsuna, Satoshi; Hayakawa, Kayoko; Shiojiri, Daisuke; Katanami, Yuichi; Yamamoto, Kei; Takeshita, Nozomi; Ohmagari, Norio
Abstract: We herein report a case of Vibrio furnissii bacteremia with bilateral lower limb cellulitis. A 53-year-old Japanese man with a mood disorder presented to our hospital with fever and a complaint of an inability to walk. Two sets of blood cultures became positive for V. furnissii . The treatment regimen was modified to ceftazidime and doxycycline. The patient recovered without relapse. Despite thorough examinations, portal of entry of V. furnissii remained unclear. Although the bacteria was first misidentified as V. fluvialis by the phenotyping assay (API rapid ID 32E) and matrix-assisted laser-desorption/ionization time-of-flight mass spectrometry, it was later confirmed as V. furnissii by dnaJ gene sequencing.